Results of the Mathematics Teaching Activities on Solving Exponential Equations and Exponential Inequalities Using Polya’s Problem-Solving Process for 11th Grade Students - PHOMMANITH, Khamsone; KEOPHASITH, Vatsana (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aimed to study: 1) the mathematical problem-solving ability on solving exponential equations and exponential inequalities taught using the Polya problem-solving process for 11th grade students, 2) the academic achievement of students after learning about solving exponential equations and exponential inequalities using the Polya problem-solving process, and 3) the students’ satisfaction towards learning about exponential equations and exponential inequalities using the Polya problem-solving process. The target group used in the research was 41 students’ grade 11/2 studying at PasaThipatay Secondary School, Luang Prabang Capital, Luang Prabang Province. The target group was selected conveniently. The research instruments were: the lesson plan based on Polya’s problem-solving process, the post-test, and the student satisfaction questionnaire. Data analysis was performed using Excel 2019 and SPSS V.22.0 were used for data analysis. The statistics used were mean, standard deviation, and hypothesis testing (T-test) with One sample test. The research found that: 1. All students have the ability to solve mathematical problems at a fair level. When considering the level of ability, it can be seen that there are 21 students who scored at the Excellent level, which is 51.21%, 14 students who scored at the good level, which is 34.14%, and 6 students who scored at the Fair level, which is 14.63%. 2. The academic achievement of students after studying the topic of solving exponential equations and exponential inequalities using Polya's problem-solving process is higher than the set criteria, with statistical significance at the 0.05 level. 3. Students are very satisfied with the teaching of mathematics on the topic of solving exponential equations and exponential inequalities using Polya's problem-solving process (Mean=4.46 and S.D=0.48 )